The Unimaginable Conversion of Paradise into Hell - Gurevitz, Michael (European Journal of Applied Sciences, 2024)
Our cognitive perception of ׳Paradise׳ usually portrays an attractive heavenly garden, ‘Eden’, where Adam and Eve were created (ref. 1). Quite the opposite is our imaginary picture of ‘Hell’, a concept raised at early Christianity, describing an afterlife world of punishment in flames of those being evil or living in sin during their life time.